A halogen-free flame-retardant polyamide composite material and its preparation method and application
Through the design of DOPO-like compounds coated glass fibers and free radical capture agents, combined with the combination of organic phosphinate flame retardant and synergistic flame retardant, the halogen-free flame retardant polyamide material has been solved with low GWIT and aging resistance. and the problem of insufficient mechanical properties, a halogen-free flame-retardant polyamide composite material with high GWIT, excellent aging resistance and mechanical properties is achieved.
Patent Information
- Application Number
- CN202311513801.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-11-14
AI Technical Summary
The existing halogen-free flame retardant polyamide materials have low glow wire ignition temperature (GWIT) and cannot meet the performance requirements of plastic parts in household appliances. At the same time, their aging resistance and mechanical properties are also insufficient.
Through the design of DOPO-like compounds coated glass fibers and free radical capture agents, combined with the combination of organic phosphinate flame retardant and synergistic flame retardant, the GWIT and resistance of halogen-free flame retardant polyamide composite materials have been significantly improved. Aging performance and excellent mechanical properties.
It significantly improves the GWIT of halogen-free flame-retardant polyamide composite material, enhances its aging resistance and mechanical properties, can maintain color stability under long-term photooxygen aging conditions, and has excellent moisture and heat resistance, satisfying electronic and electrical appliances and energy storage. performance needs in industries such as connectors.
Smart Images

Figure BDA0004548337480000031 
Figure BDA0004548337480000061 
Figure BDA0004548337480000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a halogen-free flame-retardant polyamide composite material and a preparation method and application thereof. Background Art
[0002] Polyamide (PA), also known as nylon, is a general term for a class of polymers containing amide repeating units in the main chain, including aliphatic polyamides, aromatic polyamides, and aliphatic-aromatic polyamides. Polyamide is one of the important thermoplastic engineering plastics. It has many excellent properties such as high strength, good self-lubrication, wear resistance, oil resistance, and easy molding and processing. It is widely used in electronic appliances, home appliances, automobiles, mechanical parts, new energy and other fields. As a typical organic polymer material, polyamide has a low oxygen index and can be ignited after contact with flames. When burning, it produces a large amount of flame droplets and releases a lot of heat and gas. Therefore, when polyamide is used in electronic appliances, automobiles, new energy and other products with fire safety requirements, flame retardant treatment is a very necessary step.
[0003] Adding flame retardants to polyamide is a common method of flame retardant treatment. Flame retardants commonly used in polyamide are mainly divided into halogen flame retardant systems and halogen-free flame retardant systems. Halogen flame retardant systems have low costs and good flame retardant efficiency, but low high temperature resistance, and release certain harmful gases while flame retardant the polymer, which cannot meet environmental protection requirements. In recent years, they have been gradually replaced by halogen-free flame retardant systems. Halogen-free flame retardant systems are mainly nitrogen-based flame retardants and phosphorus-based flame retardants, in addition to inorganic flame retardants. Among them, phosphinate flame retardants have attracted much attention as new environmentally friendly phosphorus-based flame retardants.
[0004] Studies have shown that phosphinate flame-retardant polyamide has excellent comprehensive mechanical properties, is easy to color, easy to process, and has a high tracking index (CTI). It is often used in connectors, low-voltage electrical appliances, energy storage and other industries. However, the flame retardant efficiency of phosphinate flame retardants is low when used alone, and its flame retardant mechanism is mainly condensed phase and supplemented by gas phase. Therefore, the efficiency of capturing free radicals is much lower than that of brominated flame retardants, resulting in a low glow wire ignition temperature (GWIT) of phosphinate flame-retardant polyamide, which cannot meet the performance requirements of plastic parts in household appliances.
[0005] In order to improve the flame retardancy and GWIT of phosphinate flame retardant polyamide, it is a common practice in the industry to use other flame retardants in combination with phosphinate flame retardants. For example, CN109694568A discloses a high glow-wire halogen-free flame retardant polyamide composite, which includes, by weight percentage: polyamide resin 40-90%, organic phosphinate flame retardant 2-25%, melamine flame retardant 1-40%, phosphate flame retardant 1-10%, reinforcing agent 0-45%, and other additives 0.1-3%. The polyamide composite uses phosphate flame retardant, melamine flame retardant and organic phosphinate together to improve the glow-wire performance and flame retardant performance, but due to the high addition amount of the flame retardant component and the poor dispersibility of the flame retardant in the polyamide resin, the mechanical properties of the material are reduced, and the aging resistance is also insufficient.
[0006] CN111315810A discloses a polyamide composition, comprising the following components: 30wt%-80wt% of polyamide, 5wt%-50wt% of inorganic fiber, and 5wt%-40wt% of flame retardant system, wherein the flame retardant system comprises zinc phosphinate and nitrogen-containing polyphosphate; the polyamide composition has a glow-wire ignition temperature of 775°C or higher, which is improved compared with the polyamide material having only the phosphinate flame retardant, but the degree of improvement is low, and GWIT still has a lot of room for improvement, and the polyamide composition is prone to discoloration after long-term light exposure and has poor aging resistance.
[0007] Therefore, developing a flame-retardant polyamide material with high glow-wire ignition temperature, good aging resistance and mechanical properties is a research focus in this field. Summary of the invention
[0008] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a halogen-free flame retardant polyamide composite material, a preparation method and application thereof, by means of a design of DOPO-type compound coated glass fiber and containing a free radical scavenger and its mutual compounding with an organic phosphite flame retardant and a synergistic flame retardant, the glow wire ignition temperature (GWIT) and aging resistance of the halogen-free flame retardant polyamide composite material are significantly improved, and it also has excellent mechanical properties.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a halogen-free flame-retardant polyamide composite material, wherein the halogen-free flame-retardant polyamide composite material comprises the following components in parts by mass:
[0011]
[0012] The present invention has been found through research that DOPO compounds, as a type of phosphaphenanthrene flame retardant containing an aromatic ring structure, have excellent carbon-forming flame retardant effects and can enhance condensed phase flame retardancy, but their single addition is likely to lead to a decrease in the mechanical properties of polyamide materials. Accordingly, the present invention coats DOPO compounds on glass fibers, effectively weakening the candle wick effect of glass fibers, and cooperates with free radical scavengers, organic phosphite flame retardants, and synergistic flame retardants to improve the flame retardancy and GWIT of halogen-free flame-retardant polyamide composite materials. At the same time, the free radical scavenger can efficiently capture various free radicals such as alkyl radicals, alkoxy radicals, and peroxy radicals generated during high-temperature degradation of polyamide, thereby improving GWIT. The present invention is based on the design of DOPO-type compound-coated glass fiber and free radical scavenger, and the compounding and mutual coordination with organic phosphite flame retardant and synergistic flame retardant, so that the halogen-free flame retardant polyamide composite material has high GWIT and excellent flame retardancy, and the aging resistance is significantly improved. It can maintain color stability under long-term light-oxidation aging conditions, and maintain excellent moisture and heat resistance and mechanical properties, which fully meets the performance requirements of electronic appliances, energy storage, connectors and other industries.
[0013] In the present invention, the term "DOPO" means 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide The term "DOPO-type compounds" includes DOPO and / or DOPO derivatives, wherein the DOPO derivatives include any one or a combination of at least two of compounds in which the H on the P atom in DOPO is replaced by other groups, compounds in which the benzene ring in DOPO is attached with substituents, and compounds in which the H on the P atom in DOPO is replaced by other groups and the benzene ring is attached with substituents.
[0014] In the halogen-free flame-retardant polyamide composite material of the present invention, the mass parts of the polyamide resin are 25-60 parts, for example, it can be 28 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or 55 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0015] The mass percentage of the DOPO-type compound coated glass fiber is 15-40 parts, for example, it can be 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts or 38 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0016] The mass parts of the organic phosphinate flame retardant are 12-30 parts, for example, 13 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 27 parts or 29 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0017] The mass fraction of the synergistic flame retardant is 3-10 parts, for example, it can be 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0018] The mass fraction of the free radical scavenger is 1-3 parts, for example, it can be 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0019] In the present invention, by designing and compounding the various components in specific amounts, the halogen-free flame-retardant polyamide composite material has both high GWIT and excellent aging resistance, and achieves an excellent balance effect in terms of mechanical properties, flame retardant properties, high GWIT and high aging resistance stability. If the mass fraction of the free radical scavenger is too low, the GWIT of the halogen-free flame-retardant polyamide composite material will be low; if the mass fraction of the free radical scavenger is too high, the halogen-free flame-retardant polyamide is prone to increased light aging color difference or easy precipitation under hot and humid conditions.
[0020] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0021] In the present invention, the polyamide resin includes any one of a condensation product of a dicarboxylic acid and a diamine, a condensation product of an ω-amino acid, and a ring-opening polymerization product of a cyclic lactam, or a combination of at least two thereof.
[0022] The dicarboxylic acid illustratively includes but is not limited to: any one of adipic acid, sebacic acid, dodecanedioic acid, terephthalic acid, and isophthalic acid, or a combination of at least two thereof.
[0023] The diamines illustratively include, but are not limited to, any one of hexamethylenediamine, decanediamine, dodecanediamine, butanediamine, p-phenylenediamine, and m-phenylenediamine, or a combination of at least two thereof.
[0024] The cyclic lactam illustratively includes, but is not limited to, any one of caprolactam, capryllactam, undecanolactam, and lauryl lactam, or a combination of at least two thereof.
[0025] The ω-amino acid illustratively includes, but is not limited to, any one or a combination of at least two of the ω-amino acids formed by the ring-opening of the aforementioned cyclic lactams and aminobenzoic acid.
[0026] Preferably, the polyamide resin includes any one of polyamide 6 (polycaprolactam, PA6), polyamide 11 (PA11), polyamide 12 (PA12), polyamide 66 (polyhexamethylene adipamide, PA66), polyamide 610 (PA610), polyamide 612 (PA612), polyamide 1010 (PA1010), polyamide 1012 (PA1012), and polyamide 1212 (PA1212), or a combination of at least two of them.
[0027] Preferably, the relative viscosity of a concentrated sulfuric acid solution of the polyamide resin at a concentration of 0.01 g / mL at 25° C. is 2.0-3.4, for example, it may be 2.1, 2.3, 2.5, 2.7, 2.9, 3, 3.1 or 3.3, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0028] Exemplarily, the relative viscosity test method is as follows: weigh 0.5g of polyamide resin, transfer it to a 50mL volumetric flask, add about 40mL of concentrated sulfuric acid (the mass percentage of H2SO4 is 96%), and ultrasonically oscillate until the polyamide resin is completely dissolved, cool the solution to 25°C, dilute it to the scale with concentrated sulfuric acid, and mix it evenly. Test the flow time of 0.01g / mL of polyamide resin solution through the Ubbelohde viscometer at 25°C, recorded as t1, and use the same viscometer to test the flow time of the solvent concentrated sulfuric acid, recorded as t2, t1 / t2 is the relative viscosity of the polyamide resin.
[0029] Preferably, the DOPO compound in the DOPO compound-coated glass fiber has a structure as shown in Formula I:
[0030]
[0031] In formula I, R is selected from any one of hydrogen, substituted or unsubstituted C1-C10 straight or branched alkyl, and substituted or unsubstituted C6-C20 aryl.
[0032] The substituents in R are selected from hydroxyl, halogen, carboxyl, amino, nitro, C2-C6 ester or At least one of the groups, the dotted line represents the attachment site of the group.
[0033] Wherein, the C1-C10 straight chain or branched alkyl group can be a straight chain or branched alkyl group of C1, C2, C3, C4, C5, C6, C7, C8, C9, C10, illustratively including but not limited to: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-methylbutyl, n-pentyl, isopentyl, neopentyl, n-hexyl, neohexyl, 2-ethylhexyl, n-octyl, n-heptyl, n-nonyl, n-decyl, etc.
[0034] The C6-C20 aryl group may be an aryl group of C6, C9, C10, C12, C14, C16, C18, etc., and illustratively includes but is not limited to: phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, phenanthrenyl, indenyl, fluorenyl and its derivative groups, fluoranthenyl, triphenylene, pyrenyl, peryl, Base, tetraphenyl, etc.
[0035] The halogen includes fluorine, chlorine, bromine or iodine.
[0036] The ester group can be understood as COOR 11 , where R 11 It may be a C1-C5 (eg, C1, C2, C3, C4, C5) straight chain or branched chain alkyl group.
[0037] Preferably, the DOPO compound includes 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO, )、9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-hydroxymethyl-10-oxide (ODOPM, )、10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide (DP-HQ, ) or a combination of at least two thereof, with DOPO being more preferred.
[0038] Preferably, the glass fiber in the DOPO-based compound coated glass fiber includes any one of alkali-free glass fiber (E glass fiber), high alkali glass fiber (A glass fiber), special glass fiber (S glass fiber), D glass fiber, medium alkali glass fiber (C glass fiber), and quartz glass fiber, or a combination of at least two of them, and alkali-free glass fiber (E glass fiber) is further preferred.
[0039] Preferably, the diameter of the glass fiber is 1-30 μm, for example, it can be 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm or 28 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 5-15 μm is further preferred.
[0040] Preferably, in the DOPO-type compound coated glass fiber, based on the mass of the glass fiber as 100%, the mass of the DOPO-type compound is 1%-5%, for example, it can be 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 4.5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values included in the said range, and 2%-4% is further preferred.
[0041] In the present invention, the coating amount = 100% × the mass of DOPO compounds / the mass of glass fiber; that is, the coating amount of DOPO compounds in the DOPO compound-coated glass fiber is preferably 1%-5%, and more preferably 2%-4%. Thus, the DOPO compound can form a uniform and effective coating on the glass fiber, which, on the one hand, significantly inhibits the wick effect of the glass fiber and enables the DOPO compound to form a good dispersion effect in the polyamide system. On the other hand, the DOPO compound-coated glass fiber (especially the DOPO compound) cooperates with the organic phosphite flame retardant, the synergistic flame retardant, and the free radical scavenger, so that the halogen-free flame retardant polyamide composite material has high GWIT, excellent flame retardancy, excellent aging resistance and excellent mechanical properties. If the coating amount of DOPO compounds is too low, the glass fiber cannot be effectively coated, and the effect of improving the GWIT of the halogen-free flame retardant polyamide composite material is not obvious; if the coating amount of DOPO compounds is too high, the aging resistance of the halogen-free flame retardant polyamide composite material will be reduced, the stability will be insufficient, and the color difference after the light-oxidation aging experiment will be large.
[0042] Exemplarily, the coating amount of the DOPO-type compound coated glass fiber can be tested by the following method: respectively testing the mass m1 of the glass fiber before coating and the mass m2 of the DOPO-type compound coated glass fiber after coating, coating amount = 100% × (m2-m1) / m1.
[0043] Preferably, the length of the DOPO-type compound coated glass fiber is 100-800 μm, for example, it can be 200 μm, 300 μm, 400 μm, 500 μm, 600 μm or 700 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 200-600 μm is further preferred.
[0044] As a preferred technical solution of the present invention, the DOPO-type compound coated glass fiber enters a melt blending device (such as a screw extruder, preferably a twin-screw extruder) in the form of continuous long fibers, and is sheared by the device to form short-cut DOPO-type compound coated glass fibers with an average length of 100-800 μm, more preferably 200-600 μm, which exist in the halogen-free flame-retardant polyamide composite material.
[0045] The present invention does not impose any particular limitation on the preparation method of DOPO compound-coated glass fiber. Any method known in the art for coating DOPO compound on the surface of glass fiber to obtain the DOPO compound-coated glass fiber is applicable to the present invention.
[0046] Exemplarily, the DOPO-type compound coated glass fiber is prepared by the following method, which includes: allowing the glass fiber to enter from the inlet of a coating device loaded with molten DOPO-type compound, and pulling it out from the outlet by a pulling device to obtain the DOPO-type compound coated glass fiber.
[0047] Preferably, the internal temperature of the coating device is 160-220°C, for example, it can be 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C or 215°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 170-200°C is further preferred; this temperature keeps the DOPO compound in the coating device in a molten state.
[0048] Preferably, the pulling speed of the pulling device is 5-50 cm / s, for example, 8 cm / s, 10 cm / s, 15 cm / s, 20 cm / s, 25 cm / s, 30 cm / s, 35 cm / s, 40 cm / s or 45 cm / s, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the above range. By controlling the pulling speed, the DOPO compound coating amount can be controlled, and the DOPO compound coated glass fiber with different DOPO compound coating amounts can be prepared.
[0049] Preferably, the organic phosphinate flame retardant has a structure as shown in Formula II:
[0050]
[0051] In formula II, R1 and R2 are each independently selected from any one of C1-C6 straight chain or branched alkyl and C3-C6 cycloalkyl; wherein the C1-C6 straight chain or branched alkyl can be a straight chain or branched alkyl of C1, C2, C3, C4, C5, C6, illustratively including but not limited to: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-methylbutyl, n-pentyl, isopentyl, neopentyl, n-hexyl, neohexyl, etc.; the C3-C6 cycloalkyl can be a cycloalkyl of C3, C4, C5, C6, such as cyclopropyl, cyclobutyl, cyclopentyl or cyclohexyl.
[0052] In Formula II, M n+ It represents a +n-valent metal ion, where n is 2 or 3.
[0053] Preferably, R1 and R2 are each independently selected from any one of a C1-C4 straight chain or branched chain alkyl group and a cyclohexyl group.
[0054] Preferably, the M n+ Selected from Al 3+ or Zn 2+ .
[0055] Preferably, the organic phosphinate flame retardant includes any one of aluminum diethylphosphinate, aluminum dipropylphosphinate, aluminum methylethylphosphinate, aluminum methylbutylphosphinate, aluminum methylcyclohexylphosphinate, and zinc diethylphosphinate, or a combination of at least two thereof.
[0056] Preferably, the organic phosphinate flame retardant comprises aluminum diethylphosphinate.
[0057] Preferably, the synergistic flame retardant includes any one of melamine polyphosphate, melamine aluminum polyphosphate, melamine magnesium polyphosphate, melamine zinc polyphosphate, and zinc borate, or a combination of at least two thereof, and melamine polyphosphate and / or zinc borate are further preferred.
[0058] Preferably, the free radical scavenger includes any one of aromatic secondary amines, phosphites, hindered phenols, and hindered amines, or a combination of at least two thereof, and aromatic secondary amines are more preferred.
[0059] As a preferred technical solution of the present invention, the free radical scavenger includes an aromatic secondary amine. On the first aspect, the aromatic secondary amine can efficiently capture various free radicals such as alkyl radicals, alkoxy radicals, peroxy radicals, etc. generated during the high-temperature decomposition of the polymer, thereby improving the GWIT; on the second aspect, the aromatic secondary amine forms a hydrogen bond with the DOPO compound in the DOPO compound-coated glass fiber based on the H on the secondary amine group, thereby synergistically enhancing the effect and further improving the GWIT of the halogen-free flame retardant polyamide composite material. At the same time, the aging resistance stability of the aromatic secondary amine is also improved. Moreover, the halogen-free flame retardant polyamide composite material containing the aromatic secondary amine has excellent moisture and heat resistance stability, and the aromatic secondary amine will not migrate and crystallize on the surface of the material.
[0060] Preferably, the aromatic secondary amine includes any one of 4,4'-di(phenylisopropyl)diphenylamine, octylated diphenylamine, 4,4'-di(α,α-dimethylbenzyl)diphenylamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N-phenyl-N'-cyclohexyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, N-phenyl-1-naphthylamine, N-phenyl-2-naphthylamine, 4,4'-diisooctyldiphenylamine, and N,N'-di(2-naphthyl)p-phenylenediamine, or a combination of at least two thereof.
[0061] Preferably, the phosphite includes any one or a combination of at least two of bis(2,4-dicumylbenzene)pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, dioctadecylpentaerythritol diphosphite, 2,2',2"-nitrilo(triethyl-tris(3,3',5,5'-tetra-tert-butyl-1,1'-biphenyl-2,2'-diyl))phosphite, tetrakis(2,4-di-tert-butylphenyl-4,4'-biphenyl)bisphosphite, tetrakis(2,4-di-tert-butylphenyl)-4,3'-diphenylene diphosphite, and tetrakis(2,4-di-tert-butylphenyl)-3,3'-diphenylene diphosphite.
[0062] Preferably, the hindered phenol includes any one of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, triethanol bis(β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate), and thiodiethylene bis(3-(3,5-di-tert-butyl-4-hydroxy-phenyl)propionate) or a combination of at least two thereof.
[0063] Preferably, the hindered amine includes any one of poly-((6-((1,1,3,3-tetramethylbutyl)-imino)-1,3,5-triazine-2,4-diyl)(2-(2,2,6,6-tetramethylpiperidinyl)-amino)-hexamethylene-(4-(2,2,6,6-tetramethylpiperidinyl)-imino)), poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) ester, N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, or a combination of at least two thereof.
[0064] It should be noted that the polyamide composite material of the present invention may also include any other additives that are added with motivation in the art.
[0065] Preferably, the halogen-free flame-retardant polyamide composite material further comprises a nucleating agent and / or a lubricant.
[0066] Preferably, the halogen-free flame retardant polyamide composite material also includes 0.01-0.5 parts of nucleating agent by weight. For example, the mass fraction of the nucleating agent can be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts or 0.45 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0067] Preferably, the nucleating agent includes any one of talc, polyamide 22 (PA22), sodium salt of aliphatic carboxylic acid, and calcium salt of aliphatic carboxylic acid, or a combination of at least two thereof.
[0068] Preferably, the sodium salt of aliphatic carboxylic acid includes sodium salt of long carbon chain carboxylic acid, specifically sodium salt of C10-C36 (e.g., C12, C14, C16, C18, C20, C22, C24, C26, C28, C30, C32, C34, etc.) carboxylic acid.
[0069] Preferably, the aliphatic carboxylic acid calcium salt includes a long carbon chain carboxylic acid calcium salt, specifically a C10-C36 (e.g., C12, C14, C16, C18, C20, C22, C24, C26, C28, C30, C32, C34, etc.) carboxylic acid calcium salt.
[0070] Preferably, the halogen-free flame retardant polyamide composite material also includes 0.01-1 parts of lubricant by weight, and the mass parts of the lubricant can be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts or 0.9 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0071] Preferably, the lubricant includes any one of hydrocarbon lubricants, ester lubricants, alcohol lubricants, fatty acid lubricants, fatty acid amide lubricants, and metal soap lubricants, or a combination of at least two thereof, and ester lubricants are more preferred.
[0072] Preferably, the ester lubricant includes any one of fatty acid ester, polyol ester, polyethylene glycol ester, or a combination of at least two thereof.
[0073] In a preferred technical solution, the halogen-free flame-retardant polyamide composite material comprises the following components in parts by mass:
[0074]
[0075]
[0076] In the halogen-free flame retardant polyamide composite material provided by the present invention, polyamide resin is used as the main resin. Preferably, the mass percentage of the polyamide resin in the halogen-free flame retardant polyamide composite material is 40-60%, for example, it can be 42%, 45%, 48%, 50%, 52%, 55% or 58%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0077] The DOPO-type compound coated glass fiber has a reinforcing effect. Preferably, the mass percentage of the DOPO-type compound coated glass fiber in the halogen-free flame retardant polyamide composite material is 15-35%, for example, it can be 18%, 20%, 22%, 25%, 28%, 30%, 32% or 34%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0078] In a second aspect, the present invention provides a method for preparing the halogen-free flame-retardant polyamide composite material as described in the first aspect, the preparation method comprising:
[0079] Mixing a polyamide resin, an organic phosphinate flame retardant, a synergistic flame retardant and a free radical scavenger to obtain a premix;
[0080] The premix and the DOPO compound coated glass fiber are melt-blended and then extruded to obtain the halogen-free flame-retardant polyamide composite material.
[0081] Preferably, the mixed material further comprises a nucleating agent and / or a lubricant.
[0082] Preferably, the mixing is carried out in a high-speed mixer.
[0083] Preferably, the mixing time is 1-20 min, for example, it can be 2 min, 5 min, 8 min, 10 min, 12 min, 15 min or 18 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 3-10 min is further preferred.
[0084] Preferably, the mixing temperature is 15-40°C, for example, it can be 18°C, 20°C, 22°C, 25°C, 28°C, 30°C, 32°C, 35°C or 38°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and room temperature is further preferred.
[0085] Preferably, the melt blending is carried out in a screw extruder, and the screw extruder is preferably a twin-screw extruder.
[0086] Preferably, the temperature of each section of the screw barrel of the screw extruder is independently 150-280°C, for example, it can be 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C or 270°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 160-250°C is further preferred.
[0087] Preferably, the head temperature of the screw extruder is 220-280°C, for example, it can be 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C or 270°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 230-260°C is further preferred.
[0088] Preferably, the screw speed of the screw extruder is 200-1000rpm, for example, it can be 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm or 900rpm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 300-800pm is further preferred.
[0089] Preferably, the screw extruder has a screw length-to-diameter ratio of (32-52):1, for example, 36:1, 40:1, 44:1 or 48:1, etc., and more preferably (36-48):1.
[0090] Preferably, the extrusion further includes the steps of drawing, cooling and pelletizing.
[0091] In a preferred technical solution, the method for preparing the halogen-free flame-retardant polyamide composite material comprises:
[0092] A polyamide resin, an organic phosphite flame retardant, a synergistic flame retardant, a free radical scavenger, an optional nucleating agent and an optional lubricant are mixed for 3-10 minutes to obtain a premix; the premix is added to the main feeding hopper of a twin-screw extruder, and the DOPO-type compound-coated glass fiber is added from the side feeding hopper of the sixth section of the screw barrel, and after sufficient plasticization and melt blending, the premix is extruded, and the polyamide composite material is obtained through drawing, cooling and pelletizing; wherein the screw speed of the twin-screw extruder is 300-800rpm, the screw aspect ratio is (36-48):1, the temperature of each section of the screw barrel is independently 160-250°C, and the head temperature is 230-260°C.
[0093] In a third aspect, the present invention provides a use of the halogen-free flame-retardant polyamide composite material as described in the first aspect in electronic appliances, energy storage devices or connectors.
[0094] Preferably, the halogen-free flame-retardant polyamide composite material is applied to a connector.
[0095] Compared with the prior art, the present invention has the following beneficial effects:
[0096] (1) In the halogen-free flame-retardant polyamide composite material provided by the present invention, through the design and synergistic effect of DOPO-type compound-coated glass fiber and free radical scavenger, and compounded with organic phosphite flame retardant and synergistic flame retardant, the halogen-free flame retardant polyamide composite material has high GWIT and excellent flame retardancy, while the aging resistance is significantly improved, so that it can maintain color stability under long-term light-oxidation aging conditions, and has excellent mechanical properties and moisture and heat resistance, which fully meets the performance requirements of industries such as electronic appliances, energy storage, and connectors.
[0097] (2) The present invention designs and optimizes each component and cooperates with each other, so that the GWIT of the halogen-free flame-retardant polyamide composite material is ≥775°C and can reach 800°C, the color difference ΔE after xenon lamp aging for 168 hours is less than 5, the tensile strength is ≥115MPa, and there is no migration and precipitation after 85°C, 85%RH wet heat aging, thereby achieving excellent comprehensive performance of high GWIT, excellent flame retardant performance, low aging color difference, high mechanical strength, good aging stability and good wet heat stability. DETAILED DESCRIPTION
[0098] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0099] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0100] In the following specific implementation of the present invention, the specific information of the materials used is as follows:
[0101] (1) Polyamide resin
[0102] PA66, specifically PA66 EPR24, with a relative viscosity of 2.4, purchased from Shenma Group;
[0103] PA6, specifically PA6 HY2800A, with a relative viscosity of 2.8, was purchased from Haiyang Chemical Fiber.
[0104] (2) DOPO-based compounds coated glass fibers
[0105] Specifically, it is DOPO coated glass fiber, wherein the glass fiber is alkali-free glass fiber (diameter is about 10 μm), and the length of the DOPO coated glass fiber is 200-500 μm. According to the different DOPO coating amounts, there are the following specific types:
[0106] DOPO coated glass fiber A, the coating amount of DOPO is 2%;
[0107] DOPO coated glass fiber B, the coating amount of DOPO is 1%;
[0108] DOPO coated glass fiber C, the coating amount of DOPO is 5%;
[0109] DOPO coated glass fiber D, the coating amount of DOPO is 0.5%;
[0110] DOPO coated glass fiber E, the coating amount of DOPO is 8%.
[0111] (3) Glass fiber
[0112] Alkali-free glass fiber, ERS200-13-T635B, roving, was purchased from Taishan Glass Fiber Co., Ltd.
[0113] (4) DOPO: purchased from Aladdin.
[0114] (5) Organic phosphinate flame retardant
[0115] Aluminum diethylphosphinate, Exolit OP 1230, was purchased from Clariant.
[0116] (6) Synergistic flame retardants
[0117] Melamine polyphosphate, Budit 3141, was purchased from Budit.
[0118] (7) Free Radical Scavengers
[0119] Aromatic secondary amine: 4,4'-di(phenylisopropyl)diphenylamine, NAUGARD 445, purchased from SI Group;
[0120] Aromatic secondary amine: N,N'-diphenyl-p-phenylenediamine, purchased from Aladdin;
[0121] Aromatic secondary amine: N-phenyl-1-naphthylamine, purchased from Aladdin;
[0122] Phosphite: bis(2,4-dicumylbenzene) pentaerythritol diphosphite, Revonox 608, purchased from QiTi;
[0123] Hindered amine: poly-((6-((1,1,3,3-tetramethylbutyl)-imino)-1,3,5-triazine-2,4-diyl)(2-(2,2,6,6-tetramethylpiperidinyl)-amino)-hexylidene-(4-(2,2,6,6-tetramethylpiperidinyl)-imino)), CHIMASSROB 944FDL, purchased from BASF;
[0124] Hindered phenol: N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, RIANOX 1098, purchased from Rianlon.
[0125] (8) Nucleating agent
[0126] Long carbon chain carboxylic acid sodium salt, LICOMONT NAV101 PWD, was purchased from Clariant.
[0127] (9) Lubricant
[0128] Ester lubricant, TR044W, was purchased from Struktol.
[0129] Example 1
[0130] A halogen-free flame-retardant polyamide composite material and a preparation method thereof, wherein the halogen-free flame-retardant polyamide composite material comprises the following components in parts by mass:
[0131]
[0132] The preparation method of the halogen-free flame-retardant polyamide composite material is as follows:
[0133] (1) PA66 EPR24, aluminum diethylphosphinate, polyphosphate melamine, aromatic secondary amine NAUGARD 445, nucleating agent LICOMONT NAV101 PWD and lubricant TR044W were mixed in a high-speed mixer for 5 minutes according to the above formula to obtain a premix;
[0134] (2) Add the premix obtained in step (1) to the main feeding hopper of a twin-screw extruder, and add the DOPO-coated glass fiber A from the side feeding hopper of the sixth screw barrel. The screw speed of the twin-screw extruder is 400 rpm, the screw aspect ratio is 40:1, the temperatures of each section of the screw barrel are 160°C, 250°C, 240°C, 240°C, 220°C, 220°C, 220°C, 230°C, and 230°C, respectively, and the head temperature is 250°C, so that each component is fully plasticized, melt-blended, and then extruded. After drawing, cooling, and pelletizing, the halogen-free flame-retardant polyamide composite material is obtained.
[0135] Examples 2-14, Comparative Examples 1-4
[0136] A halogen-free flame-retardant polyamide composite material, which differs from Example 1 only in the types and / or amounts of components, as shown in Tables 1 and 2, wherein "--" represents that the component is not added; the preparation method of the halogen-free flame-retardant polyamide composite material is the same as that of Example 1.
[0137] Table 1
[0138]
[0139] Table 2
[0140]
[0141] The performance test of the halogen-free flame-retardant polyamide composite materials provided in Examples 1-14 and Comparative Examples 1-4 was carried out, and the specific method is as follows:
[0142] (1) Glow wire ignition temperature (GWIT): injection molded square plates of 60 mm × 60 mm × 0.8 mm were tested according to the method in standard IEC60695-2-13:2021;
[0143] (2) Xenon lamp aging color difference: Injection mold a 60mm×50mm×2.0mm square plate, test the color values according to CIE 2000, record them as L1, a1, b1, and then perform xenon lamp aging on the color plate according to ISO 4892-2cycle1. After 168h, take out the color values of the color plate test, record them as L2, a2, b2, and the color difference ΔE can be calculated by the following formula:
[0144]
[0145] (3) Mechanical properties: Injection molded ISO tensile specimens, tensile strength tested according to ISO 527-2:2012;
[0146] (4) Moisture and heat resistance: A square plate of 60 mm × 50 mm × 2.0 mm was injection molded and placed in a moisture and heat aging chamber at 85°C and 85% RH for 168 h. After the plate was taken out, the surface precipitation was observed.
[0147] The test data is shown in Table 3:
[0148] Table 3
[0149]
[0150]
[0151] According to the performance test data in Table 3, the present invention adopts the design and synergistic effect of DOPO-coated glass fiber and free radical scavenger, and compounded with diethyl aluminum phosphinate and synergistic flame retardant, and optimizes the components, so that the halogen-free flame retardant polyamide composite material provided in Examples 1-9 has significantly improved GWIT, GWIT ≥ 775 ° C, can be 800 ° C, the color difference ΔE after xenon lamp aging for 168 hours is less than 5, can be as low as 2.51-4.88, the tensile strength is ≥ 115 MPa, and there is no precipitation phenomenon after wet heat aging for 168 hours, and it has excellent aging stability, moisture and heat resistance and mechanical properties.
[0152] By comparing the performance data of Example 1 with those of Examples 12-14, it can be seen that when the free radical scavenger is an aromatic secondary amine, it forms a hydrogen bond with the DOPO in the DOPO-coated glass fiber, synergistically enhancing the effect and giving the halogen-free flame-retardant polyamide composite material a higher GWIT; if the free radical scavenger is a phosphite (Example 12), a hindered amine (Example 13), or a hindered phenol (Example 14), not only is the GWIT of the material slightly lower than that of Example 1, but the free radical scavenger will migrate during the wet heat aging process and crystallize on the surface of the material, affecting the wet heat stability of the material.
[0153] In the present invention, the coating amount of DOPO compounds in the DOPO-coated glass fiber is designed to be 1%-5%, and compounded with other components, so that the halogen-free flame-retardant polyamide composite material has high GWIT, excellent aging resistance and moisture and heat resistance. The DOPO coating amount in the DOPO-coated glass fiber of Example 10 is too low, and the GWIT is only increased by 25°C. The DOPO coating amount in Example 11 is too high, and the GWIT is improved, but the xenon lamp aging color difference is large, the aging resistance is poor, and DOPO precipitation occurs.
[0154] The present invention adopts the design and synergistic effect of coating glass fiber with a specific content of DOPO compounds and a free radical scavenger, and compounding with an organic phosphite flame retardant and a synergistic flame retardant, so that the halogen-free flame retardant polyamide composite material has high GWIT, excellent aging resistance and moisture and heat resistance. In Comparative Example 1, the free radical scavenger NAUGARD 445 was not used, and its GWIT was only 725°C. In Comparative Example 2, DOPO was not coated on the glass fiber, but was directly added, resulting in a decrease in the mechanical properties of the material, and the effect of improving GWIT was not obvious. In Comparative Example 3, the amount of free radical scavenger added was too little, and the effect of improving GWIT was not obvious; while in Comparative Example 4, the amount of free radical scavenger added was too much. Although the GWIT of the material was increased to 800°C, the xenon lamp aging color difference was as high as 7.99, and the aging resistance was deteriorated.
[0155] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the halogen-free flame-retardant polyamide composite material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A halogen-free flame-retardant polyamide composite material, characterized in that: The halogen-free flame-retardant polyamide composite material comprises the following components in parts by mass: The DOPO compound in the DOPO compound-coated glass fiber has a structure as shown in Formula I: Wherein, R is selected from any one of hydrogen, substituted or unsubstituted C1-C10 straight or branched alkyl, substituted or unsubstituted C6-C20 aryl; The substituents in R are selected from hydroxyl, halogen, carboxyl, amino, nitro, C2-C6 ester or At least one of the above, the dotted line represents the attachment site of the group; In the DOPO-based compound-coated glass fiber, the mass of the DOPO-based compound is 1%-5% based on the mass of the glass fiber being 100%; The synergistic flame retardant includes any one of melamine polyphosphate, melamine aluminum polyphosphate, melamine magnesium polyphosphate, and melamine zinc polyphosphate, or a combination of at least two thereof; The free radical scavenger includes any one of aromatic secondary amines, phosphites, hindered phenols, and hindered amines, or a combination of at least two of them.
2. The halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The polyamide resin includes any one of polyamide 6, polyamide 11, polyamide 12, polyamide 66, polyamide 610, polyamide 612, polyamide 1010, polyamide 1012, and polyamide 1212, or a combination of at least two of them.
3. The halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The glass fiber in the DOPO-based compound coated glass fiber includes any one of alkali-free glass fiber, high-alkali glass fiber, special glass fiber, D glass fiber, medium-alkali glass fiber, and quartz glass fiber, or a combination of at least two thereof.
4. The halogen-free flame-retardant polyamide composite material according to claim 3, characterized in that: The glass fiber in the DOPO-based compound coated glass fiber is an alkali-free glass fiber.
5. The halogen-free flame-retardant polyamide composite material according to claim 3, characterized in that: The diameter of the glass fiber is 1-30 μm.
6. The halogen-free flame-retardant polyamide composite material according to claim 5, characterized in that: The diameter of the glass fiber is 5-15 μm.
7. The halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: In the DOPO-based compound-coated glass fiber, based on the mass of the glass fiber being 100%, the mass of the DOPO-based compound is 2%-4%.
8. The halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The length of the DOPO compound coated glass fiber is 100-800 μm.
9. The halogen-free flame-retardant polyamide composite material according to claim 8, characterized in that: The length of the DOPO compound coated glass fiber is 200-600 μm.
10. The halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The organic phosphinate flame retardant has a structure as shown in Formula II: Wherein, R1 and R2 are each independently selected from any one of C1-C6 straight chain or branched chain alkyl and C3-C6 cycloalkyl; M n+ It represents a +n-valent metal ion, where n is 2 or 3.
11. The halogen-free flame-retardant polyamide composite material according to claim 10, characterized in that: The R1 and R2 are each independently selected from any one of a C1-C4 straight chain or branched chain alkyl group and a cyclohexyl group.
12. The halogen-free flame-retardant polyamide composite material according to claim 10, characterized in that: The M n+ Selected from Al 3+ or Zn 2+ .
13. The halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The organic phosphinate flame retardant includes aluminum diethylphosphinate.
14. The halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The synergistic flame retardant is melamine polyphosphate.
15. The halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The free radical scavenger is an aromatic secondary amine.
16. The halogen-free flame-retardant polyamide composite material according to claim 1 or 15, characterized in that: The aromatic secondary amines include any one of 4,4'-di(phenylisopropyl)diphenylamine, octylated diphenylamine, 4,4'-di(α,α-dimethylbenzyl)diphenylamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N-phenyl-N'-cyclohexyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, N-phenyl-1-naphthylamine, N-phenyl-2-naphthylamine, 4,4'-diisooctyldiphenylamine, and N,N'-di(2-naphthyl)p-phenylenediamine, or a combination of at least two thereof.
17. The halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The halogen-free flame-retardant polyamide composite material further comprises a nucleating agent and / or a lubricant.
18. The halogen-free flame-retardant polyamide composite material according to claim 17, characterized in that: The halogen-free flame-retardant polyamide composite material further comprises 0.01-0.5 parts by weight of a nucleating agent.
19. The halogen-free flame-retardant polyamide composite material according to claim 17, characterized in that: The nucleating agent includes any one of talc, polyamide 22, sodium salt of aliphatic carboxylic acid, and calcium salt of aliphatic carboxylic acid, or a combination of at least two thereof.
20. The halogen-free flame-retardant polyamide composite material according to claim 17, characterized in that: The halogen-free flame-retardant polyamide composite material further comprises 0.01-1 parts by weight of lubricant.
21. The halogen-free flame-retardant polyamide composite material according to claim 17, characterized in that: The lubricant includes any one of hydrocarbon lubricants, ester lubricants, alcohol lubricants, fatty acid lubricants, fatty acid amide lubricants, and metal soap lubricants, or a combination of at least two of them.
22. A method for preparing the halogen-free flame-retardant polyamide composite material according to any one of claims 1 to 21, characterized in that: The preparation method comprises: Mixing a polyamide resin, an organic phosphinate flame retardant, a synergistic flame retardant and a free radical scavenger to obtain a premix; The premix is melt-blended with the DOPO compound-coated glass fiber and then extruded to obtain the halogen-free flame-retardant polyamide composite material.
23. The preparation method according to claim 22, characterized in that: The mixed material also includes a nucleating agent and / or a lubricant.
24. The preparation method according to claim 22, characterized in that: The mixing time is 1-20 min.
25. The preparation method according to claim 24, characterized in that: The mixing time is 3-10 min.
26. The preparation method according to claim 22, characterized in that: The melt blending is carried out in a screw extruder.
27. The preparation method according to claim 26, characterized in that: The temperature of each section of the screw barrel of the screw extruder is independently 150-280°C.
28. The preparation method according to claim 27, characterized in that: The temperature of each section of the screw barrel of the screw extruder is independently 160-250°C.
29. The preparation method according to claim 26, characterized in that: The head temperature of the screw extruder is 220-280°C.
30. The preparation method according to claim 29, characterized in that: The head temperature of the screw extruder is 230-260°C.
31. The preparation method according to claim 22, characterized in that: The method further comprises the steps of drawing, cooling and pelletizing after the extrusion.
32. Use of the halogen-free flame-retardant polyamide composite material according to any one of claims 1 to 21 in electronic appliances, energy storage devices or connectors.
Citation Information
Patent Citations
High-glow-wire halogen-free flame-retardant polyamide compound as well as preparation method and application thereof
CN109694568A
Flame retardant polyamide composition
CN111315810A
Flame-retardant impact-resistant high-stability nylon composite material and preparation method thereof
CN109852042A
High-heat-resistance halogen-free flame-retardant polyamide compound and preparation method thereof
CN112574559A
Cited By
Nylon-SPS composition as well as preparation method and application thereof
CN122060317A